Population biology of the fiddler crab Uca maracoani (Crustacea, Ocypodidae) inhabiting an impacted mangrove area on the southern coast of São Paulo state, Brazil - Machado, Glauco B. O. [UNESP]; Gusmao, Joao B.; Marochi, Murilo Z. [UNESP]; Abessa, Denis M. S. [UNESP]; Costa, Tânia Marcia [UNESP] (Sociedade Brasileira de Carcinologia, 2021)
Fiddler crabs are important components of intertidal benthic macrofauna in estuarine habitats. However, these invertebrates often inhabit areas under anthropogenic-driven changes. In this study, we evaluated the habitat quality and the population biology of the fiddler crab Uca maracoani (Latreille, 1802) in a mangrove area under anthropogenic influence, on the southern coast of São Paulo state, Brazil. Sediment samples for ecotoxicological analyses and data on the population biology of U. maracoani were collected monthly between October 2008 and October 2009. Contamination was observed in sediment samples from all months, indicating that benthic organisms inhabiting the study area are continuously exposed to toxicity. The sex ratio did not deviate from 1:1 for the whole population of U. maracoani, within any given month (except in October 2008, when males outnumbered females). Adult males and females showed a similar size, while juvenile females were larger than juvenile males, probably reflecting that females attained sexual maturity at a larger size than males. For both juvenile and adult stages, the major cheliped propodus length and height in males and the abdomen width in females showed positive allometry. The size-frequency distribution of the studied population varied from unimodal to bimodal. Juveniles were recorded in all months, suggesting the studied population has continuous recruitment. In contrast, ovigerous females were not found in the study area for several months. Although U. maracoani is continuously exposed to contamination present in the sediment, it presents a well-established population and seems to persist in the study area.
Keywords: Allometry; crabs; ecotoxicology; pollution; population dynamics